2021
DOI: 10.3390/neurolint13010009
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Functional Connectivity between Putamen and Salience Network and Childhood Body Mass Index

Abstract: Introduction: Although the putamen has a significant role in reward-seeking and motivated behaviors, including eating and food-seeking, minorities’ diminished returns (MDRs) suggest that individual-level risk and protective factors have weaker effects for Non-Hispanic Black than Non-Hispanic White individuals. However, limited research is available on the relevance of MDRs in terms of the role of putamen functional connectivity on body mass index (BMI). Purpose: Building on the MDRs framework and conceptualizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Higher activation in the striatum and insula in response to food images were observed in children and adolescents with obesity compared to their healthy-weight peers (19)(20)(21). In the resting state, higher striatal and insular network FC was also linked to eating in the absence of hunger, food craving, disinhibited eating, weight gain and obesity in both children and adults (40)(41)(42)(43). Current ndings on FC between the hippocampus and striatum are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Higher activation in the striatum and insula in response to food images were observed in children and adolescents with obesity compared to their healthy-weight peers (19)(20)(21). In the resting state, higher striatal and insular network FC was also linked to eating in the absence of hunger, food craving, disinhibited eating, weight gain and obesity in both children and adults (40)(41)(42)(43). Current ndings on FC between the hippocampus and striatum are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the BD I patients exhibited altered DC-putamen FC. The putamen is involved in reward-seeking and motivation behaviors, including food-seeking, and its FC is associated with childhood BMI 44 . The local striatal circuitry plays a critical role in the computing of sensory, motor and limbic information into behavioral and cognitive outputs, and impaired function in terms of an amplifier or filter may induce dysfunction of lateral inhibition 45 .…”
Section: Discussionmentioning
confidence: 99%